Digitizing government - Brown, Alan W. 1962-; Fishenden, Jerry; Thompson, Mark (Business in the digital economy, 2014)
"For businesses large and small, investment in digital technologies is now a priority essential for success. Digitizing Government provides practical advice for understanding and implementing digital transformation to increase business value and improve client engagement. This easy-to-read book is organized into "why", "what", and "how" sections and examines the major elements of digital transformation, with clear steps for improved execution of digital strategies. It features case studies from the private and public sectors, and a detailed chronology of digital change efforts across the UK government sector, and relates that to government efforts in the USA and around the world. It provides a practical and unique set of insights into business in the digital economy"..